Peranan Lingkungan Eksternal Internal Terhadap Kinerja Industri Kecil Batik di Kabupaten Bangkalan - Yustina Chrismardani; Triana Setiyarini (Trunojoyo University of Madura, 2008)
The performance of every kind of industry always related to external-internal environment. Based on that subject, this research aimed to analyze the influences of external environment factors (buyers, suppliers, techology and government) and internal environment factors (marketing, finance and production) to the performance of small business of batik in Bangkalan. The population of this research was the small business’s manager or owner in Kecamatan Tanjung Buli Kabupaten Bangkalan. The sample was 42 batik’s manager or owner, taken in 3 villages. The result of this research was : buyers, suppliers, technology, marketing and production had the significant influences to the small business’s performance; and marketing had the biggest influence to the small businesss’s performance.